The Effect of Solution Treatment on Mechanical Properties and Micro Structure of Zr-10Ti-Sn Alloy for Screw Dental Implant Application - Utami, Deva Ayu; Mulyani, R. Henny; Prajitno, Djoko Hadi (International Journal of Mechanical Engineering Technologies and Applications, 2021)
The research was to investigate the effect of solution treatment on the mechanical properties and microstructure of Zr-10Ti-Sn alloy for dental implant biomaterials. The addition of titanium as a material has good corrosion resistance and stannum as a material has a low modulus young and can increase hardness of the alloy in accordance with the material criteria as a dental implant, which must have good corrosion resistance and good mechanical properties. Zr -10Ti-xSn alloy (x = 0, 2, and 4% wt) were subjected to solution treatment with temperature variations of 900oC, 1000oC and 1100oC with water quenching. The results  is increase in stannum content can also increase the hardness because stannum can inhibit the enlargement of grain boundaries and the microstructure is more homogeneous and tends to be smaller with an uniaxial shape. Stannum as alpha stabilizer will form a hard alpha phase. Micro Vickers hardness test with the highest hardness value of 601,438 HV alloy Zr-10Ti-2Sn with 900oC solution treatment, phases formed were α-Zr and β-Zr and intermetallic Zr4Sn and SnTi3 Zr-10Ti-4Sn alloys which were identified using X-Ray Diffraction (XRD).